2018
DOI: 10.1103/physrevb.97.184517
|View full text |Cite
|
Sign up to set email alerts
|

Raising the superconducting Tc of gallium: In situ characterization of the transformation of α -Ga into β -Ga

Abstract: Gallium (Ga) displays several metastable phases. Superconductivity is strongly enhanced in the metastable β-Ga with a critical temperature Tc = 6.04(5) K, while stable α-Ga has a much lower Tc < 1.2 K. Here we use a membrane-based nanocalorimeter to initiate the transition from α-Ga to β-Ga on demand, as well as study the specific heat of the two phases on one and the same sample. The in-situ transformation is initiated by bringing the temperature to about 10 K above the melting temperature of α-Ga. After such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…• Metastability: An ample number of examples have been recently reported, in which metastability adds an extra dimension in the phase diagram of several systems: elemental phosphorus [74]; barium [91] and gallium under pressure [496]; tinnitrides under pressure [497]; PdH [442]; PH 2 [168]; LaH x [3,181]; metastable charge-density-wave superconductors [498] as well as oxides [499,500]. These works showed that controlled heating and cooling cycles or pressure-hysteresis cycles permit to selectively stabilize different metastable phases.…”
Section: Optimizing Tc and Pressure In Hydridesmentioning
confidence: 99%
“…• Metastability: An ample number of examples have been recently reported, in which metastability adds an extra dimension in the phase diagram of several systems: elemental phosphorus [74]; barium [91] and gallium under pressure [496]; tinnitrides under pressure [497]; PdH [442]; PH 2 [168]; LaH x [3,181]; metastable charge-density-wave superconductors [498] as well as oxides [499,500]. These works showed that controlled heating and cooling cycles or pressure-hysteresis cycles permit to selectively stabilize different metastable phases.…”
Section: Optimizing Tc and Pressure In Hydridesmentioning
confidence: 99%
“…At ambient pressure, the highest temperature superconductivity of a clearly conventional sort (with w 1) is MgB 2 , which does not appear in the figure because it has such a high Θ D = 884 K, and thus has T c /Θ D = 0.04 [11]. This suggests that if a way can be found to increase the value of λ in this material, it Data on the various materials were obtained from the following references: elements from [3,4]; A-15s from [5], Skutterudites from [6,7,8]; CaC 6 from [9]; BKBO from [10]. In most cases estimates of Θ D were obtained from low-temperature specific-heat measurements, in others it was estimated from e.g.…”
Section: Experimental Determination Of K B T C / ωmentioning
confidence: 99%
“…Because of its cost effectiveness and accessibility, Ga is an interesting material in phase transition (PT) studies. Ga also shows a promising potential in monatomic PC memory devices for data storage, superconductivity, metamaterial, and reversible adhesion . To reverse the supercooling of liquid Ga, external perturbations are applied to induce nucleation and subsequent crystal growth .…”
mentioning
confidence: 99%
“…Ga also shows a promising potential in monatomic PC memory devices for data storage, superconductivity, metamaterial, and reversible adhesion . To reverse the supercooling of liquid Ga, external perturbations are applied to induce nucleation and subsequent crystal growth . Even though molecular liquids are promising candidates to study phase transformation at ambient pressures and moderate temperatures, it is rather difficult to practically monitor the exact site of nucleation, since nucleation is a stochastic process …”
mentioning
confidence: 99%
See 1 more Smart Citation